Messenger RNA structure and gene regulation at the translational level in Escherichia coli: the case of threonine:tRNAThr ligase. - Moine, H (1988)
Previous work showed that the expression of the Escherichia coli threonine:tRNAThr ligase (EC 6.1.1.3)-encoding gene (thrS) is negatively autoregulated at the translational level and that a region called the operator that is located between 10 and 50 base pairs upstream of the translation initiation codon of the thrS gene is directly involved in that control. The conformation of an in vitro synthesized RNA fragment extending over the thrS regulatory region has been investigated using chemical and enzymatic probes. This study shows that the RNA folds into four well-defined secondary-structure domains, one of them displaying structural similarities to the anticodon arm of tRNAThr. The conformation of three constitutive mutants containing single base changes in the operator region leading to the loss of the regulatory control was also investigated. The replacement of a base in the anticodon-like loop does not induce any conformational change, suggesting that the residue concerned is directly involved in the regulatory process. However, single mutations in or close to the anticodon-like stem result in a partial or complete reorganization of the structure of the operator region. These rearrangements should affect the binding of the ligase to the operator, leading to loss of the regulatory process.